Problems In The Transition From Pre-School To Primary School: Readiness And Maturity Of Children's Learning From Pre-School To Primary School (Grade 1 SDN 32 Dompu) - Rahmah, Rahmah; Ruslan, Ruslan; Nasaruddin, Nasaruddin (Jurnal Ilmiah Wahana Pendidikan, 2025)
Children's readiness to enter school is a very important thing to consider when children are going to enter elementary school, especially in terms of readiness to receive lessons. If the transition process fails, the next learning process will also fail. Those who must be ready in this transition process are parents, children and schools where the child continues elementary school. This study was conducted to determine the readiness of children's learning maturity from PAUD to elementary school level. This study is a descriptive qualitative study. The subjects of this study were children, parents and teachers in elementary school grade 1. Data collection techniques through interviews and questionnaires as the main data collection. This study also conducted observations and documentation as supporting data. The results of this study indicate that children's learning maturity readiness includes physical and mental readiness, social emotional, cognitive and language. In addition to these factors, the age and motivation of students are also the causes of children's learning maturity readiness in elementary school